P PENGARUH PROMOSI, PERSEPSI HARGA DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN PADA APLIKASI SHOPEE: Promosi mempengaruhi keputusan pembelian, Persepsi Harga mempengaruhi keputusan pembelian, Kepercayaan mempengaruhi keputusan pembelian - Rina Ayu Vildayanti; ADAWIYAH, ROBIYATUL (Fakultas Ekonomi Universitas Kadiri, 2024)
The purpose of this study is to determine the influence of Promotion, Price Perception and Trust on Purchasing Decisions. This research is a quantitative research by distributing questionnaires to 100 respondents from students of the Faculty of Economics and Business, Budi Luhur University Jakarta, calculated using the accidental sampling method. The research instrument is in the form of a questionnaire with Likert Scale. The results of respondents' answers to the questionnaire given were then processed using SPSS Software version 21. The results showed that promotion, price recession and trust variables had a significant influence on purchasing decisions.